PRESYNAPTIC AND POSTSYNAPTIC MECHANISMS INVOLVED IN TETANIC FADE INDUCED BY PANCURONIUM IN THE ISOLATED RAT MUSCLE - Gallacci, M.; Oliveira, A. C. (Karger, 1994)
The mechanisms underlying the fade of the tetanic contraction induced by pancuronium were studied in vitro by means of myographical and electrophysiological techniques in the extensor digitorum longus muscle of the rat. Pancuronium (0.5 mu mol/l) induced a complete fade of the tetanic contraction while leaving the twitch unaffected. At the same concentration it decreased the amplitude and increased the tetanic rundown of trains of endplate potentials (e.p.ps) evoked in the frequency of 50 Hz. The electrophysiological changes induced by pancuronium were due to decreases in both quantal sizes and quantal contents of the e.p.ps. The former effect was the result of a postsynaptic competitive action and the latter of a presynaptic inhibitory action of that compound. The decrease in quantal. content affected the e.p.ps starting from the first in the train and became larger during the generation of the sequence of e.p.ps. This intensified their tetanic rundown. It is concluded that the fade of the tetanic contraction induced by pancuronium is due to a summation of pre- and postsynaptic actions and, therefore, not only to an increase in the tetanic rundown of e.p.ps. Possible explanations for the distinct abilities of neuromuscular blockers in affecting tetani and twitches in a differential manner are also discussed.
Keywords: PANCURONIUM; NEUROMUSCULAR JUNCTION, RAT; END-PLATE POTENTIALS; TETANIC FADE MECHANISMS